Digital photogrammetry: An experience of processing aerial photograph of UTM acquired using digital camera - Ahmad, Anuar (2010)
In GIS, aerial photograph can be used as a source of input to the system. The aerial photograph can be in the form of metric or non-metric imagery. In aerial photogrammetry, for most applications aerial photograph acquired using large format (230mmx230mm) is used. However, sometime there is a need to use small format aerial photograph which can be acquired using small format camera. Digital camera is a small format camera that can be used to acquire aerial photograph (non-metric imagery). This paper discusses about the experience of processing aerial photograph which is acquired using a high resolution SLR digital camera and a digital photogrammetric system. For the non-metric digital images a digital camera was used to acquire more than ten digital images to cover approximately the same area covered by a pair of photograph of a metric camera. For the digital camera, it was calibrated using a test field after the acquisition of aerial photography. Ground control points were established using Global Positioning System (GPS). After setting up the stereomodel using digital images of the digital camera, on screen digitizing was carried out. Then the results were exported to a CAD software or Geographical Information System (GIS) software for further action. From the experience of processing the non-metric imagery using the digital photogrammetric system, it was found that the system is capable of processing the digital images easily, could be used for photogrammetric education, research and consultation work. This system could be used not only by photogrammetrist, however, it could also be used by other professionals such as engineers, planners, scientist and others.